A Wavelet OFDM receiver for baseband power line communications. Issue 7 (May 2016) - Cruz-Roldán, Fernando; Pinto-Benel, Freddy A.; Osés del Campo, José D.; Blanco-Velasco, Manuel
Abstract: Wavelet OFDM is one of the medium access techniques adopted by the IEEE P1901 working group for broadband power line communications (PLC). This paper reviews important aspects of baseband physical layer for broadband PLC, such as the scheme of modulation to obtain the transmitter and the characteristics of the recommended prototype filters. It further proposes a viable receiver system compatible with the transmitter and that provides perfect reconstruction characteristics in ideal environments. Furthermore, a procedure to perform the per-subcarrier frequency domain equalization, essential to deal with the power line channel effects at the receiver side, is also addressed. In order to greatly simplify the equalizer design, an efficient fast algorithm with reduced computational complexity is presented. Finally, this study is completed with several computer simulations, considering in-home PLC scenarios, to demonstrate the benefits of the proposed transceiver system.